If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 4)(x + 4) = 8 Reorder the terms: 3(4 + x)(x + 4) = 8 Reorder the terms: 3(4 + x)(4 + x) = 8 Multiply (4 + x) * (4 + x) 3(4(4 + x) + x(4 + x)) = 8 3((4 * 4 + x * 4) + x(4 + x)) = 8 3((16 + 4x) + x(4 + x)) = 8 3(16 + 4x + (4 * x + x * x)) = 8 3(16 + 4x + (4x + x2)) = 8 Combine like terms: 4x + 4x = 8x 3(16 + 8x + x2) = 8 (16 * 3 + 8x * 3 + x2 * 3) = 8 (48 + 24x + 3x2) = 8 Solving 48 + 24x + 3x2 = 8 Solving for variable 'x'. Reorder the terms: 48 + -8 + 24x + 3x2 = 8 + -8 Combine like terms: 48 + -8 = 40 40 + 24x + 3x2 = 8 + -8 Combine like terms: 8 + -8 = 0 40 + 24x + 3x2 = 0 Begin completing the square. Divide all terms by 3 the coefficient of the squared term: Divide each side by '3'. 13.33333333 + 8x + x2 = 0 Move the constant term to the right: Add '-13.33333333' to each side of the equation. 13.33333333 + 8x + -13.33333333 + x2 = 0 + -13.33333333 Reorder the terms: 13.33333333 + -13.33333333 + 8x + x2 = 0 + -13.33333333 Combine like terms: 13.33333333 + -13.33333333 = 0.00000000 0.00000000 + 8x + x2 = 0 + -13.33333333 8x + x2 = 0 + -13.33333333 Combine like terms: 0 + -13.33333333 = -13.33333333 8x + x2 = -13.33333333 The x term is 8x. Take half its coefficient (4). Square it (16) and add it to both sides. Add '16' to each side of the equation. 8x + 16 + x2 = -13.33333333 + 16 Reorder the terms: 16 + 8x + x2 = -13.33333333 + 16 Combine like terms: -13.33333333 + 16 = 2.66666667 16 + 8x + x2 = 2.66666667 Factor a perfect square on the left side: (x + 4)(x + 4) = 2.66666667 Calculate the square root of the right side: 1.632993163 Break this problem into two subproblems by setting (x + 4) equal to 1.632993163 and -1.632993163.Subproblem 1
x + 4 = 1.632993163 Simplifying x + 4 = 1.632993163 Reorder the terms: 4 + x = 1.632993163 Solving 4 + x = 1.632993163 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + x = 1.632993163 + -4 Combine like terms: 4 + -4 = 0 0 + x = 1.632993163 + -4 x = 1.632993163 + -4 Combine like terms: 1.632993163 + -4 = -2.367006837 x = -2.367006837 Simplifying x = -2.367006837Subproblem 2
x + 4 = -1.632993163 Simplifying x + 4 = -1.632993163 Reorder the terms: 4 + x = -1.632993163 Solving 4 + x = -1.632993163 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + x = -1.632993163 + -4 Combine like terms: 4 + -4 = 0 0 + x = -1.632993163 + -4 x = -1.632993163 + -4 Combine like terms: -1.632993163 + -4 = -5.632993163 x = -5.632993163 Simplifying x = -5.632993163Solution
The solution to the problem is based on the solutions from the subproblems. x = {-2.367006837, -5.632993163}
| 2t-3t=0 | | 42-5x=4x+21 | | -105-10=8x-21 | | 2x+8-7x=43 | | 5U-3=28 | | 11y-5=7y-41 | | 11x-145=5x-13 | | 6n-4(n+3)=34 | | 84=2(35)+2w | | 50-4x=5x+17 | | 7=x(3+10x)-6x | | 1.4+1=10 | | -6=b+18 | | 2.25(4x+-4)=2+10x+12 | | 9a+4a-6b-4a= | | 16+10=3x+5-2x+6x | | 350+25d=67d+25d | | 2.25(4x-4)=2+10+12 | | 6=x-8 | | -12(k-1)=-(3k-6) | | 9w+10w-8w= | | 2x+8-7x=48 | | 7z-5z-4z= | | 20+20+3g+2g=115 | | x(2)=-121 | | 2x+3=19-3x | | 2b+4b+5b= | | 8+3x+2x=23 | | 5(x-4)+2(x+1)=3(2-4) | | 14-2q-5=-2q+9 | | -8v-4v= | | -3*-5=51 |